Patterns of Acid Base Balance and Plasma Electrolyte Concentrations in Post Surgical Digestive Patients - T. Murad El Fuad; Efori Gea; Chaerul Yael; Munar Lubis (Indonesian Pediatric Society Publishing House, 2019)
Patterns of acid-base balance and plasma electrolyte concentrations of postsurgical digestive patients were studied retrospectively. The patients were treated at the Pediatric ICU Dr. Pirngadi Hospital, Medan, during the period of February 1991 through January 31 1992. There were 131 patients admitted to the Pediatric ICU, 67 (51.1 %) of them had had gastrointestinal surgery. Arterial blood gas and I or plasma electrolyte examinations were done in 92% of patients within 12 hours of admission. In 50 patients both blood gas and electrolyte concentration values were examined; 6 of them died. One out of 14 patients who had only serum electrolyte concentration values died. One out of 3 patients who had neither blood gas nor plasma electrolyte concentration values died. Acid-base imbalances were found in 66% of those 50 patients, consisting of 28% metabolic acidosis, 12% respiratory alkalosis, 8% respiratory acidosis, and 6% metabolic alkalosis. Hyponatremia was found in 68.4% of the survivors and in 2 out of 6 patients who died. No hypernatremia was found in any of the patients. Hypokalemia was found in 24.6% of patients survived; and none in those who died. Hyperkalemia was encountered in 24.6% of those who survived. The overall mortality of patients who had undergone gastrointestinal surgery in the Pediatric ICU, Pirngadi Hospital, was 8/67 (11.9%).